Diversity and phosphate solubilization by bacteria isolated from Laki Island coastal ecosystem - SRI WIDAWATI (Biodiversitas Journal of Biological Diversity, 2011)
Widawati S. (2011). Diversity and phosphate solubilization by bacteria isolated from Laki Island coastal ecosystem. Biodiversitas 12: 1721. Soil, water, sand, and plant rhizosphere samples collected from coastal ecosystem of Laki Island, Jakarta, Indonesia were screened for phosphate solubilizing bacteria (PSB). While the population was dependent on the cultivation media and the sample type, the highest bacterial population was observed in the rhizosphere of Ipomoea aquatica. The PSB strains isolated from the sample registered 18.59 g-1 L-1. 18.31 g-1 L-1, and 5.68 g-1 L-1 of calcium phosphate (Ca-P), Al-P and rock phosphate solubilization after 7-days. Phosphate solubilizing capacity was the highest in the Ca-P medium. Two strains, 13 and 14, registered highest phosphomonoesterase activities (2.01 µgNP.g-1.h-1 and 1.85NP µg.g-1.h-1) were identified as Serratia marcescens, and Pseudomonas fluorescens, respectively. Both strains were isolated from the crops of Amaranthus hybridus and I. aquatica, respectively, which are commonly observed in coastal ecosystems. The presence of phosphate solubilizing microorganisms and their ability to solubilize various types of phosphate species are indicative of the important role of both species of bacteria in the biogeochemical cycle of phosphorus and the plant growth in coastal ecosystems.